Downregulation of Uncoupling Protein 2(UCP2) Mediated by MicroRNA-762 Confers Cardioprotection and Participates in the Regulation of Dynamic Mitochondrial Homeostasis of Dynamin Related Protein1 (DRP1) After Myocardial Infarction in Mice - Liu, Dehui; Zou, Shangrong; Li, Guangnan; Zhang, Qiyu; Chen, Chunlin; Li, Cuizhi; Song, Huafeng; Chen, Shaoxian; Wang, Jiawen; Wu, Yueheng; Liu, Youbin (Frontiers in Cardiovascular Medicine, 2022)
Acute myocardial infarction (MI) is one of the leading causes of death in the world, and its pathophysiological mechanisms have not been fully elucidated. The purpose of this study was to investigate the role and mechanism of uncoupling protein 2 (UCP2) after MI in mouse heart. Here, we examined the expression and role of UCP2 in mouse heart 4 weeks after MI.. The expression of UCP2 was detected by RT-PCR and western blotting. Cardiac function, myocardial fibrosis, and cardiomyocyte apoptosis were assessed by echocardiography and immunohistochemistry. Phosphatase dynamin-related peptide1(P-DRP1) and myocardial fibrosis-related proteins were measured. Cardiomyocytes were exposed to hypoxia for 6 hours to mimic the model of MI. Mdivi, an inhibitor of P-DRP1, was used to inhibit DRP1-dependent mitochondrial fission. Mitochondrial superoxide, membrane potential, oxygen consumption rate, and cardiomyocyte apoptosis were detected after hypoxia. It is shown mitochondrial superoxide, membrane potential, oxygen consumption rate, and cardiomyocyte apoptosis were dependent on the level of P-DRP1.. UCP2 overexpression reduced cardiomyocyte apoptosis （fibrosis） , improved cardiac function and inhibit the phosphorylation of DRP1 and the ratio of P-DRP1/ DRP1.However, inhibition of DRP1 by mdivi did not further reduce cell apoptosis rate and cardiac function in UCP2 overexpression group. In addition, bioinformatics analysis, luciferase activity, and western blot assay proved UCP2 was a direct target gene of microRNA-762，a up-regulated microRNA after MI. In conclusion, UCP2 plays a protective role after MI and the mechanism is involved in microRNA-762 upstream and DRP1-dependent mitochondrial fission downstream.